Meningkatkan Kesejahteraan Anak Dengan HIV/AIDS Melalui Learning and Psychological Support: A Higscope-based Approach di Kabupaten Kebumen - Muhammad Dani Ayubi; Novanda Alim Setya Nugraha; Teguh rahmat Syahputra; Raysa Salsabila; Mochamad Dafa Irkham Maulana; Nopri Anita Libertiana Saragih; Rehan Nur Setiawan; Riezky Aditya Anggaramukti (STIKes Ibnu Sina Ajibarang, 2024)
The large amount of discrimination against children with HIV/AIDS in Kebumen Regency causes many problems from the social, economic and educational spheres for the victims. They are not getting their rights which should receive protection and education because of this discrimination. In this case, special attention is needed from the Kebumen Regency Regional Government in addressing this problem. The SPARKLE program aims to provide learning and psychological assistance to those affected by discrimination to help fulfill their rights as children to receive education and the right not to be discriminated against. This program is collaborated with the Finnish curriculum module (Highscope) which focuses on their interests and talents during mentoring. This is because the child's age and background do not allow them to follow theoretical learning. Therefore, it is necessary to use varied, creative and interesting methods so that participants remain focused on learning. In this way, mentoring will be effective in increasing their interest in living a life that previously was always haunted by the discrimination they received.